The use of Postponement Decisions in Determining Supply Chain Strategies of Light Vehicle Manufacturers in South Africa - Intaher Marcus Ambe (Journal of Economics and Behavioral Studies, 2017)
This article investigates the use of postponement decisions in determining the supply chain strategies of light vehicle manufacturers in South Africa. The article is exploratory and descriptive in nature. A survey was conducted among light vehicle manufacturers and the findings analysed by means of descriptive statistics. The results revealed that postponement decisions could be used to determine the supply chain architecture used by light vehicle manufacturers in South Africa. With regard to postponement decisions, the study found that all the light vehicle manufacturers made use of a lean supply chain strategy, while a few made use of an agile supply chain strategy. The results also revealed that all the production lines engaged in full speculation based on projected forecasting, and therefore employed a lean supply chain strategy. In terms of the postponement decisions made in line with the parent company of origin, European manufacturers 1 and 2 kept a work-in-progress inventory of stock to be customised for a particular customer. These manufacturers thus employed a lean and agile supply chain strategy, while most of the manufacturers adopted a lean supply chain strategy. All the manufacturers, except Asian manufacturer 1 and the American manufacturer, employed both lean and agile supply chain strategies. Therefore, the majority of the light vehicle manufacturers employed lean supply chain strategies in their inbound and outbound supply chain, while a few employed an agile supply chain strategy in their outbound supply chain, there by indicating leaglity. The article provides evidence of some form of postponement practice being followed by light vehicle manufacturers.